Experiences of Older Adults Preparing for Their First Triathlon: "A Qualitative Study of the Participation in an Endurance Training Intervention.". Issue 1 (1st January 2021) - Johansen, Bjørn Tore; Brynjulfsen, Trine; Lohne Seiler, Hilde; Klungland Torstveit, Monica; Berntsen Stølevik, Sveinung
ABSTRACT: Purpose : The overall aim of the present study was to explore the experiences of older adult exercisers participating in an individualized training program lasting 3 months preparing for completing a triathlon competition. Methods: Fourteen older Norwegian adults (median age (interquartile range, IQR) for males (N=10) and females (N=4) were 70.0 (65.0-75.5) and 57.5 (56.3-62.5) years, respectively) participated in 3-month individualized training program comprising three weekly sessions of running, cycling, and swimming. Both field- and laboratory-based testing were conducted. The participants attended two sports nutrition and competitive psychology seminars focusing on triathlon competition. The participants were interviewed in depth in three different focus groups. Thematic analysis was utilized to analyze the findings. Results: Participants improved their performance in all field-based tests. After completion of the thematic data analysis the main finding and overarching theme of well-being and being fit emerged. Additionally, three main themes were identified: 1) motivation ; 2) progress and coping ; and 3) breaking barriers . Conclusion: Psychological well-being and satisfaction of being fit seem to be vital to participate in a triathlon competition. Promoting specific age-appropriate participation in sports activities can be an effective strategy for promoting a healthy lifestyle among the elderly.